EDTA-enhanced transport of copper from contaminated soil and its implications : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Soil Science at Massey University - Thayalakumaran, Thabonithy (Massey University, 2002)
An understanding of the interacting physical and chemical processes involved is necessary for efficient and environmentally responsible remediation of copper-contaminated soils through EDTA-enhanced mobilisation, using either ex situ or in situ methods. In order to study these processes, leaching experiments were performed on repacked columns and intact cores, with various initial and boundary conditions, in two contrasting soils containing varying amounts of copper. One soil was an alluvial Manawatu fine sandy loam, which was low in organic matter, and the other a volcanic Opotiki sandy loam with a higher organic matter content. In both soils, the EDTA moved without any observable adsorption when the soil pH was above 5.0. But, uncontaminated Opotiki soil with a pH of 4.5, did adsorb EDTA to some extent. Leaching with an excess of 0.01 M EDTA, extracted all but 40 mg kg-1 of the copper that was initially present in the repacked Manawatu soil and all but 90 mg kg-1 of the copper from the Opotiki repacked soil. In the intact Opotiki soil cores the EDTA reduced the copper concentration in the top 25 mm of the intact core from 240 to 80 mg kg-1. EDTA not only leached the copper from the soil, but also a substantial amount of iron. Opotiki soil with pulses of EDTA left in it for up to a month before leaching showed a time-dependent drop in the amount of copper leached, and a corresponding increase in the amount of iron leached. Increased EDTA residence time in the Manawatu soil prior to leaching in general also showed a time-dependent increase in iron leached. With increasing EDTA residence time in the soil, the mass of copper leached dropped markedly in the low-Cu Manawatu soil. However, the copper remained in the soil solution, and so prone to leaching, for at least a month in the medium and high-Cu Manawatu soils. These results are consistent with CuEDTA2- being gradually transformed to the more stable Fe(III)EDTA- and Cu2+ in all cases. Copper contaminated Opotiki repacked soil columns and intact cores growing the grass Agrostis tenuis on were used to investigate the relative importance of plant uptake and leaching of copper. Application of 1800 µmol of EDTA to 0.9 kg of the contaminated soil in a repacked column increased the leaf copper concentration from 30 µg g-1 to 300 µg g-1. The same amount of EDTA applied to 1.0 kg of soil in the intact cores, increased the herbage copper concentration to 60 µg g-1. Leaching the columns and cores with water about a month after the EDTA application removed 25 to 169 times more copper than was taken up by the herbage. The convection dispersion equation (CDE), coupled with a source/sink term accounting for time-dependent reactions taking chemical species into or out of solution, was used to model the EDTA-enhanced transport of copper in contaminated soils. In general, the model successfully described the copper concentration in the leachate and soil, despite the quite different amounts and concentrations of EDTA applied, and the varying lengths of time it was left in the soil before leaching. However, the values for the key parameters had to be adjusted appropriately, with faster rate constants for the Manawatu soil than the Opotiki soil. The observed differences in behavior between the repacked and intact Opotiki soil could be simulated by increasing the dispersivity from 3 to 23 mm, while leaving unchanged the parameters describing the chemistry. The results on the kinetics of the EDTA and the soil copper reaction, and for the stability of the CuEDTA2- and its interaction with physical processes, suggest that in situ remediation of copper contaminated soils is possible. However, the applied EDTA should be leached immediately or within few days. It would also require that the residence time of soil water moving through the profile to the water table was in excess of a month. EDTA-enhanced phytoremediation of copper might be possible if leaching can be avoided. If drainage occurs the copper moving below the root zone is likely to be at least an order of magnitude greater than that taken up by the vegetation.
Keywords: Ethylenediaminetetraacetic acid; Soil remediation; Copper contamination; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300100 Soil and Water Sciences::300103 Soil chemistry